TRANSFORMATION OF TOPOGRAPHIC DATA VISUALIZATION FROM FREEHAND DRAWING TO CARTOGRAPHIC REPRESENTATION - Perdana, Aji Putra; Juniati, Eli; Hidayat, Joni (GEOMATIKA, 2013)
Topographic data visualization has been changed into geodatabase cartography. So far, freehand drawing has been used to visualize topographic data. Unfortunately, freehand drawing does not connect its graphical features with its database, meaning that the attributes data not exist in the freehand drawing. Meanwhile, the existing cartographic rules for map representations still based on the freehand drawing and this is become a great challenge to transform these rules into geodatabase cartographic data visualization. The geodatabase cartography and its representation should be defined first in order to follow the existing rules and analyze it. On the other hand, there is another challenge related to human resource capability to understand the transformation process from drawing method into geodatabase cartography. This paper explores the transformation of topographic map visualization and its geodatabase design.Keywords: cartography, topographic map, geodatabase, cartographic representationABSTRAKVisualisasi data topografi dalam hal ini Peta Rupabumi mulai berubah dengan menggunakan geodatabase kartografi. Sejauh ini, penggambaran peta dengan freehand telah digunakan untuk mendesain tampilan peta topografi. Namun demikian, freehand tidak mempunyai kemampuan untuk menggabungkan data grafik dengan basis datanya, yang berakibat pada hilangnya atribut data. Sementara itu, aturan tampilan kartografi yang ada masih dibuat berdasarkan software freehand, dan hal ini menjadi tantangan besar untuk mentransformasikan ke dalam tampilan kartografi berdasarkan basis data geospasial (geodatabase). Untuk memenuhi aturan yang sudah ada, geodatabase kartografi dan tampilannya harus didefinisikan terlebih dahulu dan kemudian dianalisis. Di lain pihak, terdapat tantangan lain terkait dengan kemampuan sumberdaya manusia untuk memahami proses transformasi dari metode menggambar ke geodatabase kartografi. Makalah ini mengkaji proses transformasi dari visualisasi peta topografi dan desain geodatabasenya.Kata Kunci: kartografi, peta rupabumi, geodatabase, tampilan kartografi